Planejamento, registro e avaliação: instrumentos que ressignificam a prática docente na educação infantil - Ramos, Rafaela de Morais (2016)
The research “Planning, registration and evaluation: instruments that resignify teaching practice in children education” was developed in Pos-Graduation Program of the Master degree course in Education in Early Childhood Education of Centro de Ensino e Pesquisa Aplicada à Educação/CEPAE in the Universidade Federal de Goiás, in the research area “Theoretical and methodological conceptions and teaching practices”. The question that instigates the research was: Does the teacher critically linked what plans, registrate and evaluate in order to use them as tools of analysis and reflection of their pedagogical practice? This study had as object the interrelation between planning, registration and evaluation. The locus chosen for this research was the DEI/CEPAE/UFG. The research had as general objective understand if the teacher plan, execute and do the registration articulately, critically and if use this pedagogical instruments in order to analyze and evaluate their pedagogical do. The specific objectives were: a) verify in what way theses three instruments are developed; b) indentify if the registrations allows the analysis and evaluation of their pedagogical do; c) verify if the planning is based on registrations and evaluations made; d) substantiate theoretically the knowledge about planning, registration and evaluation. Defined the historical materialist dialectical method to fundament all the way of this research, understanding that this method is configured as a philosophical basis of analysis and comprehension of the world and reality. About the method, the theoreticals basis that supports the research were: Marx and Engels (1982); Vigostki (1987); Luria (1988); Triviños (2006). The methodology used was action-research (Severino, 2007), which favored different types of interactions for a dynamic reality apprehension process in order to change it. In the theoretical reference that addresses the didactic, early childhood education and childhood in historical dialectical perspective we use the following authors: Libâneo (1991); Ostetto (2000); Corsino (2009); Vigostski (1998), Luria (2012) and Leontiev (2012). The chapters of the data analysis are based on the sociohistorical authors, who also support the pedagogical proposal of DEI/CEPAE. The teaching practices of the Department of Early Childhood Education guide the learning development in the Historic-cultural approach, whose representatives are Vygotsky (1998), Wallon (2012), Leontiev (2012) and Luria (2012). Their studies conceive the child development as a historical phenomenon not determined by universal natural laws. From the analysis of the plans, registrations and evaluations of the three participating teachers of the research, it was understood that the interrelation between the three instruments needs common categories as the theoretical conception that guides the work of the teachers - the historical cultural. Explain the complexity of this dialectic triad is a challenge, however we attempted to face it during the research and, at the end of it realized that the interrelation between planning, registration and evaluation requires the teacher a critical and reflexive posture capable of resignify their own practice appropriating the knowledge and promoting the pedagogical praxis.